Gene transfer to rat cerebral cortex mediated by polysorbate 80 and poloxamer 188 nonionic surfactant vesicles - Attia N; Mashal M; Soto-Sánchez C; Martinez-Navarrete G.; Fernández E; Grijalvo S; Eritja R; Puras G; Pedraz JL (Dove Medical Press, 2018)
Noha Attia,1–3,* Mohamed Mashal,1,* Cristina Soto-Sánchez,4,5 Gema Martínez-Navarrete,4,5 Eduardo Fernández,4,5 Santiago Grijalvo,4,6 Ramón Eritja,4,6 Gustavo Puras,1,4 Jose Luis Pedraz1,4,* 1NanoBioCel Group, Laboratory of Pharmaceutics, School of Pharmacy, University of the Basque Country (UPV/EHU), Vitoria-Gasteiz, Spain; 2Medical Histology and Cell Biology Department, Faculty of Medicine, University of Alexandria, Alexandria, Egypt; 3Department of Basic Sciences, The American University of Antigua-College of Medicine, Coolidge, Antigua and Barbuda; 4Networking Research Centre of Bioengineering, Biomaterials and Nanomedicine (CIBER-BBN), Vitoria-Gasteiz, Spain; 5Neuroprothesis and Neuroengineering Research Group, Miguel Hernández University, Elche, Spain; 6Institute of Advanced Chemistry of Catalonia (IQAC-CSIC), Barcelona, Spain *These authors contributed equally to this work Background: Gene therapy can be an intriguing therapeutic option in wide-ranging neurological disorders. Though nonviral gene carriers represent a safer delivery system to their viral counterparts, a thorough design of such vehicles is crucial to enhance their transfection properties.Purpose: This study evaluated the effects of combined use of two nonionic surfactants, poloxamer 188 (P) and polysorbate 80 (P80) into nanovesicles – based on 2,3-di(tetradecyloxy)propan-1-amine cationic lipid (D) – destined for gene delivery to central nervous system cells.Methods: Niosome formulations without and with poloxamer 188 (DP80 and DPP80, respectively) were prepared by the reverse-phase evaporation technique and characterized in terms of size, surface charge, and morphology. After the addition of pCMS-EGFP plasmid, the binding efficiency to the niosomes was evaluated in agarose gel electrophoresis assays. Additionally, transfection efficiency of complexes was also evaluated in in vitro and in vivo conditions.Results: In vitro experiments on NT2 cells revealed that the complexes based on a surfactant combination (DPP80) enhanced cellular uptake and viability when compared with the DP80 counterparts. Interestingly, DPP80 complexes showed protein expression in glial cells after administration into the cerebral cortices of rats.Conclusion: These data provide new insights for glia-centered approach for gene therapy of nervous system disorders using cationic nanovesicles, where nonionic surfactants play a pivotal role. Keywords: gene therapy, nonviral gene vectors, poloxamer 188, niosomes, cationic lipids